PENGARUH KEPRIBADIAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI KEMENAG KOTA MALANG - Mukaffi, Zaim; Nuntufa, Nuntufa (IQTISHODUNA, 2014)
Someone’s personality has a strong influence on other person’s OCB. This study aims to determinethe effect neuroticism, extraversion, openness, agreeableness and conscientiousness the employee’s OCB ofKemenag (Religious Ministry) of Malang. This study used quantitative methods, the data obtained withquestioner given to 48 respondentsinthe Kemenag (Religious Ministry) of Malang. Methods of data analysisusing multiple linear regression that includes test Validity and Reliability, Testing assumptions Classical, Ftestand t-test were assisted by SPSS16:00 For Windows. The results of the simultaneous analysis of thesignificant level of 5% neuroticsm variables, extraversion, and openness to experience, agreeableness andconscientiousness effect on employee’s OCB of Kemenag (Religious Ministry) Malang. The results of partialanalysis by a significant level of 5% neuroticism no effect on employee’s OCB of Kemenag (Religious Ministry)Malang because probability value greater than 0.05 is 0.791, whereas extraversion, openness, agreeablenessand conscientiousness have a significant effect on employee’s OCB Kemenag (Religious Ministry) of Malangwith a probability value respectively .000, .000, 0.001, and 0.013.VARIABEL the dominant influence on employee’sOCB Kemenag (Religious Ministry) of Malang is agreeableness to count 3,744 with a t significant value is0.001.